EFFECTS OF LATERITE ON STRENGTH AND DURABILITY OF REINFORCED CONCRETE AS PARTIAL REPLACEMENT OF FINE AGGREGATE - Garba, Isah; Kaura, Jibrin Mohammed; Sulaiman, Tasiu Ashiru; Aliyu, Ibrahim; Abdullahi, Musa (FUDMA Journal of Sciences, 2024)
Throughout the world, concrete is widely utilized in buildings, and due to a rise in construction activity, there is a growing requirement for fine aggregate. This study aims to examine how laterite, which replaces some fine aggregate in reinforced concrete, affects the material’s strength and durability. The physical properties of materials were investigated. The compressive strength and flexural strength of laterized concrete were determined for each replacement level of 0, 10, 20, 30 and 40% at a mix ratio of 1:2:4 and a water-cement ratio of 0.65, while for the water absorption, the percentages replacement of laterite to fine aggregates was 0, 10, and 20 % with the same mix ratio and water cement ratio. A 100 X 100 X 100 mm cube and 100 X 100 X 350 mm beams were tested for compressive and flexural strength at 7, 14, 21 and 28 days of curing respectively. Water absorption was determined at 28, 56 and 90 days of curing age. The findings show that as the percentage of laterite substitution increases, the laterized concrete’s workability declines. However, the strength properties of the concrete partially replaced with laterite increase with curing age and decrease as the laterite content increases. Moreover, the water absorption of laterized concrete is increased by the inclusion of laterite. It was concluded that the use of laterite in the production of concrete should not be more than 10 %.